3D bioprinted tissue-specific spheroidal multicellular microarchitectures for advanced cell therapy. (3rd September 2021) - Park, Yejin; Ji, Seung Taek; Yong, Uijung; Das, Sanskrita; Jang, Woong Bi; Ahn, Geunseon; Kwon, Sang-Mo; Jang, Jinah
Abstract: Intercellular interaction is the most crucial factor in promoting cell viability and functionality in an engineered tissue system. Of the various shapes available for cell-laden constructs, spheroidal multicellular microarchitectures (SMMs) have been introduced as building blocks and injectable cell carriers with substantial cell–cell and cell–extracellular matrix (ECM) interactions. Here, we developed a precise and expeditious SMM printing method that can create a tissue-specific microenvironment and thus be potentially useful for cell therapy. This printing strategy is designed to manufacture SMMs fabricated with optimal bioink blended with decellularized ECM and alginate to enhance the functional performance of the encapsulated cells. Experimental results showed that the proposed method allowed for size controllability and mass production of SMMs with high cell viability. Moreover, SMMs co-cultured with endothelial cells promoted lineage-specific maturation and increased functionality compared to monocultured SMMs. Overall, it was concluded that SMMs have the potential for use in cell therapy due to their high cell retention and proliferation rate compared to single-cell injection, particularly for efficient tissue regeneration after myocardial infarction. This study suggests that utilizing microextrusion-based 3D bioprinting technology to encapsulate cells in cell-niche-standardized SMMs can expand the range of possible applications.